Reading Comprehension Skills through Workplace Education - Massachusetts Career Development Inst., Springfield; Massachusetts Career Development Inst., Springfield ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This document contains a competency-based workplace literacy curriculum that is intended to develop workers' reading comprehension skills by building on their prior knowledge and integrating job-related reading materials actually used by workers on the job with other academic reading materials and textbooks. Designed to be used in conjunction with the commercially produced Barnett Loft Specific Reading Skills Series, the curriculum consists of six units that are each based on actual texts used in real workplaces. Learners read the texts and complete accompanying exercises designed to foster development of the following reading comprehension skills: locate an answer, detect a sequence, follow directions, get facts, use the context, get the main idea, and draw conclusions. Each unit contains the following: lesson plan, exercises and accompanying narratives, exercise answers, and competency test. A variety of exercise formats are included, including open-ended questions, multiple choice questions, and fill-in-the blank exercises. Lesson plans contain the following: competency, objective, lesson outline, methodology, and resources. The following topics are covered in the texts: personal development, workplace health and safety, problem solving, team building, quality assurance, and total quality management. (MN)
Sponsoring Agency: Office of Vocational and Adult Education (ED), Washington, DC. National Workplace Literacy Program.
ERIC Note: For related documents, see CE 077 418-419 and CE 077 431-436.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Behavioral Objectives; Competency Based Education; Education Work Relationship; Individual Development; Integrated Curriculum; Learning Activities; Literacy Education; Occupational Safety and Health; Problem Solving; Reading Comprehension; Reading Processes; Reading Skills; Reading Strategies; Skill Development; Teamwork; Total Quality Management; Workplace Literacy; Quality Assurance; Guides, Classroom -- Learner